Analisis Implementasi Permainan Tradisional Sebagai Sarana Pendidikan Karakter untuk Siswa di SD Negeri 1 Demulih - Luh Candra Mitha Utami (Lembaga Pengembangan Kinerja Dosen, 2024)
Student character is not only determined by academic achievement, but also by strong morals and ethics, where character education plays a key role in this. This study focuses on the implementation of traditional games as a means of character education at SD Negeri 1 Demulih. The approach used in this study is descriptive qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that traditional games such as Meong-meongan, Guwak-guwakan, and Poh-pohan are effective in developing student character, especially in aspects of cooperation, responsibility, and sportsmanship. Before this activity was implemented, many students showed individualistic attitudes and lack of empathy. However, after the implementation of traditional games, there was a significant increase in social interaction, the ability to work in groups, and mutual respect among students. However, to achieve more optimal results, it is necessary to improve facilities and clearer instructions regarding the implementation of traditional games. This study concludes that traditional games are an effective tool for student character education.